Analysis of Web-Education Based on ISO/IEC 9126-4 for the Measurement of Quality of Use - Marzuki Marzuki; Agus Sukoco; Ahmad Cucus; Maria Shusanti Febrianti; Lisa Devilia (Bandar Lampung University (UBL), 2012)
FIK UBL Website is the website of the Faculty of Computer Science education at the University of Bandar Lampung.Domain name from FIK website UBL is www.fik.ubl.ac.id.FIK website is a subdomain of the UBL website www.ubl.ac.id.The website uses ac.id as Country Code Top level domains, domain primarily UBL, and Third-level domain is the FIK.UBL has FIK Website Hosting Server at Nusanet provider.In terms of design websites using CMS jg FIK UBL, the CMS Lokomedia.Scientific Writing will specifically focus on the analysis of UBL-based FIK website ISO / IEC 9126-4 for the use of quality measurement.In this regard, in ISO / IEC 9126-4, there are 4 metrics used to measure, among other effectiveness metrics, productivity metrics, security metrics, and Satisfaction Metrics.More specific explanation will describe in Chapter IV the author of scientific writing is about the quality of the use of UBL FIK website.